OBSERVATIONS ON THE RELATIONSHIP BETWEEN NEUROSECRETION AND PERIODIC ACTIVITY IN THE MUSSEL, PARREYSIA CORRUGATA - Nagabhushanam, R; Lomte, V S (Indian Journal of Fisheries, 2011)
Two types of ’neurosecretory cells in the freshwater mussel Parreysia corrugata are briefly described. The cell type A which is pyrifown secretes material in the fomm of colloid. The cell type B is oval and; the secretory material is in the foirm of fine grawutea Im both the ceW types transport of the secretiary materiel was noticed. Type A cells showed a distinct annual cycle of activity that is correlated to the sexual cycle.